Anti-inflammatory and anti-nociceptive property of Capparis tomentosa Lam. root extracts. (10th May 2020) - Tekulu, Gebretsadkan Hintsa; Hiluf, Teref; Brhanu, Hailu; Araya, Ephrem Mebrahtu; Bitew, Helen; Haile, Tesfay
Abstract: Ethnopharmacological relevance: Capparis tomentosa Lam. root is one of the commonly used traditional medicines for the treatment of pain and inflammatory conditions by the Kunama ethnic group of Ethiopia. Yet, its ethnomedicinal claim has not been scientifically investigated. Aim of the study: This study aims to evaluate the anti-inflammatory and anti-nociception activities of root extracts of Capparis tomentosa Lam. Materials and methods: The anti-inflammatory activity of the 70% ethanolic extracts and solvent fractions was determined using in vitro hyaluronidase inhibition assay and in vivo carrageenan-induced paw edema in Swiss albino mice model. The anti-nociception effect was determined using the acetic acid-induced writhing model and tail immersion model in Swiss albino mice. Results: The root extract of Capparis tomentosa has exhibited significant hyaluronidase inhibition activity which was comparable with the reference drug, indomethacin. Significant inhibition of carrageenan-induced paw edema was observed in all the test sample treated mice compared to the negative control with the highest activity observed from butanol fraction which was equivalent to the effect of acetylsalicylic acid. All the root extract and solvent fractions have possessed a significant and dose-dependent abdominal writhing inhibition with the highest effect observed in the aqueous fraction. Additionally, the crude extract was found better in increasing the reaction latency of the mice to the hot water stimulus than the solvent fractions which were significant after 60–120 min compared to the distilled water treated group. The root extract and solvent fractions were also found safe at a single oral dose of 2 mg/g in Swiss albino mice. Conclusion: The findings of the present study may partially support the folkloric use of Capparis tomentosa root for the treatment of pain and inflammation. Graphical abstract: Image 1